Fixed-dose combination bictegravir, emtricitabine, and tenofovir alafenamide versus dolutegravir-containing regimens for initial treatment of HIV-1 infection: week 144 results from two randomised, double-blind, multicentre, phase 3, non-inferiority trials. Issue 6 (June 2020) - Orkin, Chloe; DeJesus, Edwin; Sax, Paul E; Arribas, Jose R; Gupta, Samir K; Martorell, Claudia; Stephens, Jeffrey L; Stellbrink, Hans-Jurgen; Wohl, David; Maggiolo, Franco; Thompson, Melanie A; Podzamczer, Daniel; et al.
Summary: Background: In the primary week-48 analyses of two phase 3 studies, coformulated bictegravir, emtricitabine, and tenofovir alafenamide was non-inferior to a dolutegravir-containing regimen in treatment-naive people with HIV. We report week-144 efficacy and safety results from these studies. Methods: We did two double-blind, active-controlled studies (now in open-label extension phase). Study 1 randomly assigned (1:1) HLA-B*5701-negative adults without hepatitis B virus co-infection to receive coformulated bictegravir 50 mg, emtricitabine 200 mg, and tenofovir alafenamide 25 mg, or coformulated dolutegravir 50 mg, abacavir 600 mg, and lamivudine 300 mg once daily. Study 2 randomly assigned (1:1) adults to bictegravir, emtricitabine, and tenofovir alafenamide, or dolutegravir 50 mg given with coformulated emtricitabine 200 mg and tenofovir alafenamide 25 mg. We previously reported non-inferiority at the primary endpoint. Here, we report the week-144 secondary outcome of proportion of participants with plasma HIV-1 RNA less than 50 copies per mL at week 144, by US Food and Drug Administration Snapshot algorithm, analysed in the same manner. These studies were registered with ClinicalTrials.gov, NCT02607930 and NCT02607956 . Findings: 629 participants were randomly assigned and treated in study 1 (314 to bictegravir, emtricitabine, and tenofovir alafenamide, and 315 to dolutegravir, abacavir, and lamivudine) and 645 in study 2 (327 to bictegravir, emtricitabine, and tenofovir alafenamide, 325 to dolutegravir, emtricitabine, tenofovir alafenamide). At week 144, bictegravir, emtricitabine, and tenofovir alafenamide was non-inferior to both dolutegravir-containing regimens for efficacy. In study 1, 256 (82%) of 314 participants had plasma HIV-1 RNA less than 50 copies per mL in the bictegravir, emtricitabine, and tenofovir alafenamide group and 265 (84%) of 315 in the dolutegravir, abacavir, and lamivudine group (difference −2·6%, 95% CI −8·5 to 3·4). In study 2, 262 (82%) of 320 participants had plasma HIV-1 RNA less than 50 copies per mL in the bictegravir, emtricitabine, and tenofovir alafenamide group and 273 (84%) of 325 in the dolutegravir, emtricitabine, and tenofovir alafenamide group (difference −1·9%, −7·8 to 3·9). In both studies, no participant had treatment-emergent resistance to study drugs up to week 144. All treatment regimens were well tolerated with additional exposure. Adverse events that led to study drug discontinuation were reported for no participants in the bictegravir, emtricitabine, and tenofovir alafenamide group versus five (2%) of 315 in the dolutegravir, abacavir, and lamivudine group (study 1), and six (2%) of 320 in the bictegravir, emtricitabine, and tenofovir alafenamide versus six (2%) of 325 in the dolutegravir, emtricitabine, and tenofovir alafenamide group (study 2). In study 1, statistically significant differences were observed in median changes from baseline in fasting total cholesterol (14 mg/dL vs 10 mg/dL; p=0·034), direct LDL (21 mg/dL vs 14 mg/dL; p=0·004), and total cholesterol to HDL ratio (−0·1 vs −0·3; p=0·007) at week 144; no differences were observed between groups in study 2. Weight gain was seen across all treatment groups in both studies, with no differences in median changes from baseline in weight at week 144 for either study. Interpretation: These long-term data support the use of bictegravir, emtricitabine, and tenofovir alafenamide as a safe, well tolerated, and durable treatment for people with HIV, with no emergent resistance. Funding: Gilead Sciences.